UMUNTHU THEOLOGY an introduction. - MUSOPOLE, AUGUSTINE CHINGWALA (MZUNI PR, 2022)
What is the key to understanding in a truly Malawian way? After a lifetime's theological reflection the author finds the answer in the concept of uMunthu (personhood or human-ness).